Use of leaf meal of Morus alba in feeding of laying quail (Coturnix coturnix japonica) (Revista Sistemas de Producción Agroecológicos, 2013)
This work was made with the objective to evaluate the productive, nutritional and economic behavior in laying Japanese quails (Coturnix coturnix japonica) of week 2 to 23 of laying, using meal of leaf of mulberry (Morus alba) in three leaves the substitution the commercial concentrated. 128 birds of 52 days of age were used. Completely randomized design, with four treatments (0, 10, 15 and 20% of meal of leaf of mulberry T1, T2, T3 and T4, respectively), each one with four repetitions and 8 birds by cage. Was not significant difference between the witness (T1) and the T3, in percentage of posture, food intake g/bird/day, conversion kg feed/kg eggs produced and conversion kg feed/dozen eggs produced. (P>0.05), It was observed significant difference of the weight of eggs (P
Keywords: birds; feeding; fodder trees